Śāṅkara Vedānta : eka anuśīlana : sandarbha, śāstra, evam loka - Āṅgirasa, Ramākānta, 1936- (Naṭarāja Pabliśiṅga Hāusa, 1982)
Study of the Advaita school in Hindu philosophy, as propounded by Śaṇkārācārya.